2014
DOI: 10.5455/medarh.2014.68.263-267
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition at the Time of Surgery Affects Negatively the Clinical Outcome of Critically Ill Patients with Gastrointestinal Cancer

Abstract: Introduction:Malnutrition is a frequent concomitant of surgical illness, especially in gastrointestinal cancer surgery. The aim of the study was to assess the prevalence of malnutrition in the GI cancer patients and its relation with clinical outcome. We also examined associations between the energy balance and clinical outcomes in these patients.Methods:Prospective study on 694 surgical patients treated in the ICU of the UHC of Tirana. Patients were divided into well-nourished and malnourished groups accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 42 publications
3
57
1
8
Order By: Relevance
“…Consistently, reduced peripheral lymphocyte count indicated impairment of innate cellular immunity, which was usually associated with disease severity and poor prognosis (Fogar et al, 2006; Kobayashi et al, 2012). On the other side, malnutrition is prevalent in patients with advanced cancer and associated with inferior prognosis in various cancers (Barret et al, 2011; Shpata et al, 2014). Serum albumin is a simple surrogate marker utilized as an indicator of nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, reduced peripheral lymphocyte count indicated impairment of innate cellular immunity, which was usually associated with disease severity and poor prognosis (Fogar et al, 2006; Kobayashi et al, 2012). On the other side, malnutrition is prevalent in patients with advanced cancer and associated with inferior prognosis in various cancers (Barret et al, 2011; Shpata et al, 2014). Serum albumin is a simple surrogate marker utilized as an indicator of nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively frequent, the phenomenon occurs in 20-60% of cancer patients [1][2][3] and may considerably affect the quality of life and treatment results [8]; everyone, including those treated in highly developed countries of the European Union [9], is at risk. Importantly, malnutrition requires longer hospital stays, and, as a consequence, a more lengthy and expensive treatment process [4,[10][11][12][13], which may take up to twice as long as in properly nourished patients with the same diagnosis [2].…”
Section: Discussionmentioning
confidence: 99%
“…Its causes include the loss of appetite, reduced food intake, metabolic changes due to the tumor and cancer-related chronic inflammation, as well as the side effects of cancer treatment, including surgery and chemo-and radiotherapy. In operated patients with GI cancers, malnutrition is an independent risk factor for an increased incidence of complications, nosocomial infections, and perioperative mortality [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, malnutrition in older populations is associated with adverse medical consequences that contribute to sarcopenia, morbidity and mortality . Nutrition status, as it relates to frailty in older patients, is an important area of concern, as studies have reported 40–50% of surgical patients to be malnourished on admission to hospital . As malnutrition affects postoperative complications and progress, it is important to evaluate the preoperative nutritional status.…”
Section: Introductionmentioning
confidence: 99%